Earthwork and piling works / Nik Ahmad Bakri Mohd Iburadi - Mohd Iburadi, Nik Ahmad Bakri (Universiti Teknologi MARA, Perak, 2018)
Earthwork would involve the removal of overburden to reach structurally capable earth or soil, excavation for basements and other underground structures, and to make structural fills to support floors. Also the piling works need to be done to act as a steady support for structures built on top of it. The objective of this report is to explain how the earthwork and piling work has been done at site Pejabat Kesihatan Daerah Jeli, Kelantan.